PTP4A3 Is a Prognostic Biomarker Correlated With Immune Infiltrates in Papillary Renal Cell Carcinoma - Song, Qian; Zheng, Yutian; Wu, Junzhou; Wang, Sheng; Meng, Lin; Yao, Qian; Li, Zhongwu; Lian, Shenyi (Frontiers in Immunology, 2021)
PTP4A3 plays an important role in the tumorigenesis and metastasis of multiple tumors, but its prognostic role in renal cancer is not well understood. We utilized the Oncomine and Tumor Immunoassay Resource databases to examine the differential expression of PTP4A3 in tumor tissues and normal tissues in breast, urinary tract, gastrointestinal tract and skin. Using the GEPIA and PrognoScan databases, the independent prognostic role of PTP4A3 was confirmed in clear cell renal cell cancer and papillary renal cell cancer. Expression of PTP4A3 were obviously higher in tumor tissue compare with normal tissues (P=0.028). We haven’t found the associations of PTP4A3 and clinicopathological features in our IHC cohort. Ectopic expression of PTP4A3 promotes proliferation, migration and invasion and increased the mRNA level of TGFB1 in RCC cell lines. Immunohistochemical staining indicated that the expression of PTP4A3 associates with CD3+ (P =0.037)/ CD8+ (P =0.037) intratumor TILs, not with invasive margins in renal cancer. Comprehensive analysis of immune infiltration in the TIMER database correlated PTP4A3 expression with the infiltration of B cells, CD8+ T cells, CD4+ T cells and neutrophils in both clear cell renal cell carcinoma and papillary renal cell carcinoma. PTP4A3 expression was associated with the infiltration of dendritic cells in papillary renal cell carcinoma. We further confirmed that the infiltration of B cells and CD8+ T cells was associated with poor prognosis in papillary renal cell carcinoma patients, consistent with the prognostic role of PTP4A3 in papillary renal cell carcinoma. PTP4A3 expression correlated genes involved in B cells, monocytes, M1 macrophages, Th2 and Treg cells in papillary renal cell carcinoma. These results suggest PTP4A3 as a prognostic factor with a role in regulating immune cell infiltration in papillary renal cell carcinoma.